2011
DOI: 10.1002/jobm.201000291
|View full text |Cite
|
Sign up to set email alerts
|

Screening of promoters from rhizosphere metagenomic DNA using a promoter‐trap vector and flow cytometric cell sorting

Abstract: We constructed a facilitative and efficient promoter-trap vector, pCM-EGFP, for capturing and analyzing functional promoters from environmental DNA. The pCM-EGFP vector showed good chloramphenicol sensitivity and no enhanced green fluorescent protein (EGFP) gene expression. Promoter libraries were constructed for screening promoters responding to naringenin, a key molecule released from plant roots. After electroporation, E. coli transformants were incubated in LB broth containing chloramphenicol (10 μg/ml) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Plasmid pK19mobsacB (Schäfer et al, 1994), containing oriT for conjugative mobilization and sacB (encoding the Bacillus subtilis levansucrase) as a counter-selectable marker, was used to construct three individual nagI knockout mutants in strain CJ2. Mutagenic plasmids pK19mobsacBDnagI1, pK19mobsacBDnagI2 and pK19mobsacBDnagI3 with 2 bp deletions in the nagI genes were constructed via a three-step round-PCR approach (Lee et al, 2011) as shown in Fig. 1a.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmid pK19mobsacB (Schäfer et al, 1994), containing oriT for conjugative mobilization and sacB (encoding the Bacillus subtilis levansucrase) as a counter-selectable marker, was used to construct three individual nagI knockout mutants in strain CJ2. Mutagenic plasmids pK19mobsacBDnagI1, pK19mobsacBDnagI2 and pK19mobsacBDnagI3 with 2 bp deletions in the nagI genes were constructed via a three-step round-PCR approach (Lee et al, 2011) as shown in Fig. 1a.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid pK19 mobsacB (Schäfer et al , 1994), containing oriT for conjugative mobilization and sacB (encoding the Bacillus subtilis levansucrase) as a counter-selectable marker, was used to construct three individual nagI knockout mutants in strain CJ2. Mutagenic plasmids pK19 mobsacB Δ nagI1 , pK19 mobsacB Δ nagI2 and pK19 mobsacB Δ nagI3 with 2 bp deletions in the nagI genes were constructed via a three-step round-PCR approach (Lee et al , 2011) as shown in . Briefly, nagI gene PCR amplicons with a 2 bp deletion and Hin dIII and Eco RI sites at the flanking regions were generated by PCR using two primer sets each, nagIx1F ( Hin dIII)/nagIx1R and nagIx2F/nagIx2R ( Eco RI) shown in , where ‘x’ indicates 1, 2 or 3 for nagI1 , nagI2 and nagI3 , respectively, and then were digested with Hin dIII and Eco RI (New England Biolabs).…”
Section: Methodsmentioning
confidence: 99%
“…Another example of indirect activity assay is through promoter-trap vectors where the vector contains the GFP gene but no promoter. Therefore, GFP will not be expressed until a promoter is present in the DNA fragment (Dunn et al 2003;Lee et al 2011).…”
Section: Types Of Functional Screens For Natural Product Discoverymentioning
confidence: 99%
“…For example, promoter-trap vectors have been applied to search for promoters responding to naringenin, a compound released by plant roots. FACS was used following additions of naringenin to find genes induced by the compound (Lee et al 2011). As cell sorting technology improves, phenotypes other than fluorescence could be added to the molecular toolbox.…”
Section: Types Of Functional Screens For Natural Product Discoverymentioning
confidence: 99%
“…A detailed protocol for SIGEX has been published (Uchiyama & Watanabe, 2008). However, to date, few follow up studies -except for those from the original authors (Uchiyama & Miyazaki, 2010;Uchiyama & Watanabe, 2007) -have used SIGEX for metagenomic analyses (Lee et al, 2011). Nonetheless, it is recurrently cited as a method with excellent potential for recovering novel operons from metagenomic clone libraries (Daniel, 2005;Ekkers et al, 2012;Simon & Daniel, 2011;Taupp et al, 2011;Wexler & Johnston, 2010;Yun & Ryu, 2005).…”
Section: Sigexmentioning
confidence: 99%